Medication taking behaviors among breast cancer patients on adjuvant endocrine therapy. Issue 5 (October 2015) - Kimmick, Gretchen; Edmond, Sara N.; Bosworth, Hayden B.; Peppercorn, Jeffrey; Marcom, Paul K.; Blackwell, Kimberly; Keefe, Francis J.; Shelby, Rebecca A.
Abstract Purpose To explore how symptoms and psychosocial factors are related to intentional and unintentional non-adherent medication taking behaviors. Methods Included were postmenopausal women with hormone receptor positive, stage I-IIIA breast cancer, who had completed surgery, chemotherapy, and radiation, and were taking endocrine therapy. Self-administered, standardized measures were completed during a routine clinic visit: Brief Fatigue Inventory, Brief Pain Inventory, Menopause Specific Quality of Life Questionnaire, Functional Assessment of Cancer Therapy General and Neurotoxicity scales, and Self-Efficacy for Appropriate Medication Use Scale. Regression analyses were performed to determine the degree to which demographic, medical, symptom, and psychosocial variables, explain intentional, such as changing one's doses or stopping medication, and unintentional, such as forgetting to take one's medication, non-adherent behaviors. Results Participants were 112 women: mean age 64 (SD = 9) years; 81% white; mean time from surgery 40 (SD = 28) months; 49% received chemotherapy (39% including a taxane); mean time on endocrine therapy, 35 (SD = 29.6) months; 82% taking an aromatase inhibitor. Intentional and unintentional non-adherent behaviors were described in 33.9% and 58.9% of participants, respectively. Multivariate analysis showed that higher self-efficacy for taking medication was associated with lower levels of unintentional (p = 0.002) and intentional (p = 0.004) non-adherent behaviors. The presence of symptoms (p = 0.03) and lower self-efficacy for physician communication (p = 0.009) were associated with higher levels of intentional non-adherent behaviors. Conclusions These results suggest that women who report greater symptoms, lower self-efficacy for communicating with their physician, and lower self-efficacy for taking their medication are more likely to engage in both intentional and unintentional non-adherent behaviors.